Quantitative analysis of sub-alpine grasslands in trans-Himalayan region of Manang, central Nepal - Bhatt, Shekhar C; Lekhak, Hari D (Botanica Orientalis: Journal of Plant Science, 2010)
Species composition and richness of grassland vegetation were studied in trans-Himalayan region of Manang. Two south-facing sites, both at the similar altitude (3800-4200 m asl), were selected and a total of 40 plots (10 x 10 m) with 200 quadrates (1 m x 1 m) were sampled. Altogether, 97 plant species were recorded. The similarity index between two sites was 12.37%. There was significant negative correlation between species richness and altitude in site I. Species richness did not show significant relationship with altitude in site II. Various physical and biological factors interact differently in different sites to create habitat heterogeneity which determine the distribution pattern of plant species and influence variations in species composition and diversity. Key-words: alpine region; quantitative analysis; species diversity; vegetation. DOI: 10.3126/botor.v6i0.2910 Botanica Orientalis - Journal of Plant Science (2009) 6: 47-51